Corporate strategies for Manly Plastics, Inc. - Cannen, Romulo C. (Animo Repository, 1998)
Industries are defined on the basis of needs and wants: what need, whose need and how is that need going to be satisfied. The Plastic Industry serves the needs of customers for Plastic products and services. These products and services that are produced within the industry are close substitute for each other. The industry is divided into four sectors: Packaging, Consumer products, Industrial and Agricultural & Fisheries. The environment that this paper will focus on is that of the packaging and industrial sector. The strategic group that will be analyzed is the group companies that provide contract manufacturing services to those companies who do not have the capability or capacity to make their own products.